Pengaruh Pelatihan Dan Motivasi Terhadap Produktivitas Kerja Karyawan Pada Departemen Front Office Di Mercure Bali Sanur Resort - Sadjuni, Ni Luh Gde Sri; Andini, Ni Luh Made Putri; Jata, I Wayan (Program Studi Manajemen Divisi Kamar, 2024)
This research was conducted at Mercure Bali Sanur Resort. This study aims to determine the effect of training and motivation on employee productivity in the Front Office department at Mercure Bali Sanur Resort, which is analyzed using SPSS. Respondents in this study were 35 people who were determined using saturated sample technique. Data collection was carried out by distributing questionnaires using a 5-point Likert Scale. The analysis techniques used are classical assumption test, multiple linear regresssion, t-test, F-test, and coefficient of determination. The result of this stuudy indicate that training partially has a positive and significant effect with tcount value of 2,394 > 2,037 and a t test significance value of 0,023 < 0,05. Motivation partially have a positive and significant effect with a tcount value of 2,212 > 2,037 and a t test significance value of 0,034 < 0,05. Training and Motivation simultaneously have a significant effect on employee productivity at Mercure Bali Sanur Resort which can be proven ny Fcount value of 32,37 > 2,90 and a significance value of 0,000 < 0,05. Training and motivation contribute to employee productivity by 66,9% obtained through the coefficient of determination analysis, while the remaining 33,1% is the influence of other variables not examined in this study